Pengaruh Penggunaan Media Gambar Lewat Komputer terhadap Hasil Belajar Fisika pada Siswa Kelas X Sma Negeri 3 Makassar - Mustari, Mukarramah (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2015)
This study is an experimental research, which aims to obtain information on physics learning outcomes of students of class X SMA Negeri 3 Makassar who follow the learning through the use of media images via computer and follow the conventional learning lesson year 20013/2014. Population in this research is student of class X SMA Negeri 3 Makassar. The research samples used class random technique and obtained two classes. One class is used as an experimental class that follows the learning through the use of computerized image media and one more class as a control class that follows conventional learning with a sample size of 58 students. Data processing of this research using two statistical techniques, namely: 1) Descriptive Analysis Technique to describe the characteristics of student learning outcomes of class X SMA 3 Makassar, 2) Inferential Analysis Technique with